A Relational Communication Approach to Peer Coaching. (June 2015) - Parker, Polly; Wasserman, Ilene; Kram, Kathy E.; Hall, Douglas T.
In this article, we discuss peer coaching as a relatively new form of coaching practice that expands the relational resources available to individuals focused on change. Peer coaching is a helping relationship that facilitates mutual learning and development to accomplish specific tasks or goals. It is most effective when participants establish high-quality relationships and connections by focusing on both content and process. To enhance such capability we integrate the theory of coordinated management of meaning, a relational communication approach that emphasizes how meaning and learning are created through interpersonal interactions. Coordinated management of meaning models applied in our three-step model of peer coaching demonstrate the value of their application. We then assume a balcony perspective to deepen understanding by incorporating conceptual and empirical work. We conclude by inviting scholars and practitioners to adopt our integrated model to enhance positive outcomes for both individuals and organizations.